SISTEM JAMINAN KEAMANAN PANGAN BERDASARKAN FSSC22000 versi 5.1 / ISO TS 22002-4 PADA PROSES PRINTING DIINDUSTRI FLEXIBLE PACKAGING - Sukardi (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2023)
A HACCP analysis of the printing process at one of the process steps in the Flexible packaging industry has been carried out as a hazard analysis step to determine the hazards that need to be controlled. The initial steps for making a flow chart have been carried out, which includes a flow chart of the printing process, which is the object of research. As per the ISO 22000 clauses that all food safety hazards that may occur related to the type of product, type of process, and existing process facilities are identified and recorded, a flowchart for the printing process is made in detail, including input, process, and output. This is to avoid product types, process types, and process facilities that can be overlooked during the hazard analysis process. In the HACCP analysis of the printing process, each food safety hazard has been identified and the acceptable level of the hazard has been determined. The results of the HACCP analysis on the printing process in this study have identified several process stages, from the input process to the output process. All of these stages have been analyzed for all hazards or sources of hazards, level of acceptance, hazard assessment, linkages with regulations or legislation, and determination of actions to prevent, reduce, or eliminate hazards. If the hazard assessment results in a "high" risk value and/or is related to regulations or legislation, then further analysis is carried out to determine whether a CCP is required or not. By carrying out a HACCP analysis of the printing process for the manufacture of flexible packaging, it is possible to determine the OPRP and CCP for the process, so that food safety guarantees in this process can be controlled and realized. The results of the validation process by monitoring the results of hazard measurements on residual solvent as a hazard from CCPs that have been determined in the printing process have shown that the process is under control and capable. The main findings in this study cannot be separated from the strong pillar support of GMP implementation, which is a rule or requirement from ISO/TS 22002-4 and FSSC requirements for the food packaging industry.